Diagnóstico de la tenencia de hembras caninas en la ciudad de Loja y formulación de una propuesta para el manejo técnico - Montaño Ramón, Gloria Alexandra (2016)
The diagnosis of canine females tenure accompanied by a proposal for its technical management, was made the objective was to determine the percentage of female dogs and their methods of reproduction. The approximate number of female dogs was evaluated by family survey information obtained by the owners in the city of Loja, races most commonly used for breeding, the most common reproductive diseases according to race and age. 945 surveys distributed in the urban parishes of the canton Loja was applied, the results obtained from the sample are: the population of female dogs is 65.650, with an average of 1.4 per family that are distributed in the six parishes: Sucre 36.3%; Prick 20.8%; Carigan 13.6%; San Sebastián 12.9%; El Sagrario 8.6%; El Valle 7.8% .The race with the highest number is the Mestizo with a total of 62%, followed by the French Poodle 6% and 4% Pequines. A total of 85.61% of the females are of childbearing age. As to mount 60.3% they have been subjected to breeding. Regarding the pregnancy of female dogs showed a 97.6% state of gestation. 37.4% are used or at some point in his life was used for breeding. 93.5% of females used for reproduction have been fertilized by a Natural insemination and only 6.5% by the method of artificial insemination. 42.2% have been sterilized by OVH and 57.8% is applied hormonal drug treatments. The most common reproductive diseases are pyometra with 26.5%, with 18.8% mammary tumors, Transmissible Venereal Tumor with 18.4% and dystocia with a percentage of 11.5%.